Pemanfaatan Iot (Internet Of Things ) Untuk Praktikum IPA Pada Materi Gerak Lurus Berubah Beraturan (GLBB) Dalam Pembelajaran Daring Selama Pandemi Covid-19 - Fathurrahmaniah, Fathurrahmaniah; Widia, Widia; Islamiah, Muarif; Sarnita, Fitria (Jurnal Ilmiah Mandala Education (JIME), 2021)
Title (Utilization Of Iot (Internet Of Things) For Science Practices In Conditional Straight Motion Materials (GLBB) In Online Learning During The Covid-19 Pandemic). Science subjects, in several chapters of lessons that require practicum. The application of science has been widely developed as a demonstration tool when explaining abstract science concepts. Basically, science is learning that underlies all experimental activities. Science tools that can be used as learning media are used as practicum tools or demonstration props for science material, instrumentation in universities and science material on straight motion at school. The novelty in this research is the Development of Internet-based Science Practicum Tool Of Thigs. So as to be able to develop students' interest in learning science in the midst of the covid-19 pandemic. The novelty in this research is the Development of Internet-based Science Practicum Tool Of Thigs. So as to be able to provide an alternative for online science subject practicum in the midst of the covid-19 pandemic. This research uses the R & D (Research And Development) method. The model used in this study is the ADDIE model. Meanwhile, the analysis of the implementation of the lesson plans during the learning process was 3.706 with a very good category. From the observations of 2 observers that the use of IoT is very helpful for students in understanding the concept of GLB in the midst of covid 19. This shows that in addition to improving student learning achievement, the use of the Internet of Things (IoT) can increase student interest in learning.